The sexual self-esteem inventory - short form (SSEI-SF): factor structure of the scale for the Portuguese population - Mendes, Liliana; Leonido, Levi; Carvalho, Inês; Barbosa, Ana; Martins, Ana Filipa; Ribeiro, Maria de Fátima; Morgado, Elsa (Specijalna edukacija i rehabilitacija, 2025)
Introduction. Sexuality plays a pivotal role in human life, shaping individuals’ perceptions and practices, known as sexual self-esteem, which significantly influences attitudes and behaviours. Aim. This study aimed to examine the factor structure and reliability of the Sexual Self-Esteem Inventory (SSEI) in its abbreviated form for the Portuguese population, considering five distinct aspects: Skill/Experience, Attractiveness, Control, Moral Judgment, and Adaptiveness. Method. A cross-sectional, quantitative, comparative, and correlational study with a quasi-experimental design was conducted. A total of 901 individuals aged 18 to 39 years (M = 25.52, SD = 6.27), predominantly female (67.8%), participated in the study. The factor structure was analysed via exploratory factor analysis, and instrument reliability was assessed using Cronbach’s alpha. Results. The exploratory factor analysis yielded 24 items organized into four factors - Emotional Readiness, Competence and Experience, Attractiveness, and Adaptiveness - explaining 51.99% of the total variance. All factors exhibited good internal consistency. Conclusion. Thus, the inventory demonstrated adequate factor structure and reliability and is deemed suitable for assessing self-perceptions regarding sexuality across four dimensions in a Portuguese sample.
Keywords: sexual self-esteem; young adults; sexuality; Portuguese population